2021
DOI: 10.1590/s1980-220x2020022103758
|View full text |Cite
|
Sign up to set email alerts
|

Planejamento de sucessão de lideranças em enfermagem: caminhos para sua elaboração

Abstract: RESUMO Objetivo Descrever a construção de um planejamento de sucessão de lideranças de enfermagem para uma instituição hospitalar, com base na reflexão apreciativa de enfermeiros. Método Estudo descritivo, exploratório, de abordagem qualitativa realizada com enfermeiros de um hospital público federal de ensino. A coleta de dados foi realizada em duas etapas, sendo a primeira, entrevista individual e a segunda, por mediação grupal conduzida com base no ciclo 4D e nos pressupostos da Investigação Apreciativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
2
0
3
Order By: Relevance
“…27 To effectively implement succession planning, attention should be given to developing a strategic plan, determining required skills and needs, identifying potential candidates, determining the need for interim leadership, implementing leadership development programmes, allocating resources and evaluating progress. [29][30][31][32][33] The study also found that organisational resilience is a crucial element of succession planning, which includes a focus on futurism and organisational growth. Titzer and Shirey argue that implementing succession planning can lead to important outcomes such as leadership development, cultural growth and improved organisational leadership.…”
Section: Discussionmentioning
confidence: 93%
“…27 To effectively implement succession planning, attention should be given to developing a strategic plan, determining required skills and needs, identifying potential candidates, determining the need for interim leadership, implementing leadership development programmes, allocating resources and evaluating progress. [29][30][31][32][33] The study also found that organisational resilience is a crucial element of succession planning, which includes a focus on futurism and organisational growth. Titzer and Shirey argue that implementing succession planning can lead to important outcomes such as leadership development, cultural growth and improved organisational leadership.…”
Section: Discussionmentioning
confidence: 93%
“…A coordenação de equipes de trabalho também é outra atribuição do enfermeiro atuante na gestão, como a gestão do cuidado e os protocolos para as situações de urgência e emergência, além de favorecer a valorização dos profissionais através do empoderamento. O dimensionamento da equipe de enfermagem e elaboração das escalas é de suma importância e realizada pelo enfermeiro gestor, bem como a coordenação dos serviços de educação permanente e incentivo pela busca de aperfeiçoamento para o perfil profissional (Nogueira et al, 2021).…”
Section: Bvsunclassified
“…Succession planning should also be considered a leadership development approach and aims to ensure organizational continuity, as it proposes to offer development and training possibilities to ensure that future leadership positions are properly filled. Consequently, succession planning ensures the continuation of the intellectual heritage formed by several generations of professional nurses (17,32,33) .…”
Section: Idmentioning
confidence: 99%